Pemberdayaan Usaha Ekonomi Produktif bagi Masyarakat di Jawa Gadut, Kelurahan Limau Manis, Kecamatan Pauh, Padang - Amna Suresti; Ida Indrayani; Rahmi Wati; Uyung G.S. Dinata (Warta Pengabdian Andalas, 2020)
This activity was carried out in Java Gadut, Limau Manis Village, Pauh District, Padang. West Sumatra Province. This area has the potential for culinary business because it is located around the Andalas University campus, but this business has not been explored either due to lack of knowledge on how to improve and manage the business. This activity aimed to improve and develop human resources and community empowerment efforts through various community service programs and it is hoped that this potential can be developed. This activity was carried out with counseling methods, lectures, training and provision of equipment. The results of this activity can increase entrepreneurial motivation for partners. This can be seen from the results of their response to the activities carried out, most (85%) they are satisfied with the existence of this service activity. Increasing the entrepreneurial spirit of the members of the food business is expected to increase partner income.